Flock morphing animation. (May 2014) - Wang, Xinjie; Zhou, Linling; Deng, Zhigang; Jin, Xiaogang
ABSTRACT We propose a new animation technique, called flock morphing, to create special morphing effects between two arbitrary 3D objects by combining the features of 3D morphing and flock animation. Its core idea is first to tetrahedralize the source 3D mesh and regard each tetrahedron as an agent in a flock and then continually generate the flock morphing animation until the target mesh emerges, formed by the same set of tetrahedra. By applying plausible trajectory planning scheme and smooth deformation algorithm, we demonstrate that our proposed method can simultaneously achieve visually desired morphing effects. Copyright © 2014 John Wiley & Sons, Ltd.